Memahami Dan Menerapkan Uji Korelasi Dalam Analisis Data Penelitian Pendidikan - Patimah; Zulpan; Dite Umbara Alfansuri; El Munawaroh; Muhammad Ilyas (Journal Education Innovation (JEI), 2025)
The correlation test is one of the most frequently used statistical techniques in educational research to identify the relationship between two or more variables. This article aims to provide a comprehensive understanding of the concept, types, assumptions, and applications of both parametric and non-parametric correlation tests, including Pearson, Spearman, Kendall’s tau, and point-biserial correlations. Through a review of recent literature, the author highlights the importance of selecting the appropriate correlation method based on data characteristics, testing fundamental assumptions such as linearity and normality, and interpreting results accurately without implying causation. Furthermore, this article discusses common errors in applying correlation analysis and provides recommendations for reporting results according to modern scientific standards. By understanding and correctly applying correlation tests, educational researchers are expected to produce more accurate, valid, and scientifically accountable data analyses.